What is design thinking? - Stanford, Julie; Siminoff, Ellen Tauber; O'Neill, Mia; Mailhot, Jenny (O'Reilly Media, 2017)
Design Thinking has grown increasingly popular as a go-to method for problem solving and innovation. But what is this design methodology really about and how can it work in your company? In this report, professionals from Sliced Bread Design go beyond the hype to explain the Design Thinking process, tools, and mindset-and how they use this methodology to help business clients across a wide range of domains. Through case studies with Airbnb, GE, and Toyota, you'll learn how Design Thinking can be flexibly applied to a wide variety of problems and in various stages of product development. This cohesive, user-centered framework can be used in a multitude of areas, ranging from creating something new or running a business to managing interpersonal communication. You'll learn how: Design Thinking provides a laser focus on the actual, human roots of a given problem to solve real needs at the outset The methodology's mindset emphasizes empathy, radical collaboration, thinking by doing, iteration, and embracing ambiguity Its process moves from observation through developing insights, ideating concepts, creating prototypes, and iterating based on feedback This approach can help startups, large organizations, and policy-making organizations think about and solve problems in a new way.